Rasionalisme dan Kebangkitan Umat Islam dalam Pemikiran Jamaluddin al-Afghani (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2026)
The decline of Muslim societies in the modern era is often associated with intellectual stagnation, political despotism, and a rigid understanding of religious teachings that marginalizes the role of reason. This problem became a major concern of Jamaluddin al-Afghani, a Muslim reformist thinker who emphasized rationalism as the foundation of Islamic revival. This study employs a qualitative approach with library research methods, using historical and philosophical perspectives to analyze al-Afghani’s thought. Data were collected from primary sources, including al-Afghani’s writings and publications such as Urwat al-Wuthqā, as well as secondary sources in the form of scholarly books and journal articles. The data were analyzed using descriptive-analytical techniques. The findings show that al-Afghani viewed the separation between reason and revelation, political tyranny, and disunity among Muslims as the main causes of Islamic decline. He proposed the integration of reason and revelation, educational reform, political awareness, and pan-Islamic unity as strategic solutions for Muslim revival. This study concludes that al-Afghani’s rationalist and reformist ideas remain highly relevant in addressing contemporary challenges faced by Muslim societies.